The resolution of ambiguous anaphora in english, spanish, and portuguese - Bruscato, Amanda Maraschin; Baptista, Jorge (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2023)
This study aims to determine how (a) ambiguity resolution differs in English, Spanish, and Portuguese; (b) L2 learners are influenced by their L1 regarding ambiguity resolution; and (c) the order of the clauses, (d) the salience of the anaphor, or (e) the choice of verbs may affect this process. A total of 181 people answered an online survey and selected the antecedent of the anaphor for 16 ambiguous sentences. The Position of Antecedent Strategy was tested for the three languages and the conclusion was that it applies to European and Brazilian Portuguese, but not for Spanish or English. While Spanish and English native speakers tend to interpret the subject of the subordinate clause as corresponding to the subject of the main clause, learners are influenced by their L1 and seem uncertain especially on how to resolve pronominal cataphora. Finally, we have concluded that semantics has a great influence on the resolution of ambiguous anaphora in these languages, and we suggest that it should be taken in consideration during the design of a study like this one.